IMPACT ASSESSMENT OF TARIFF REDUCTION IN SUGAR MARKET IN TURKEY - Fatma İlknur ÜNÜVAR; İlkay DELLAL (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The aim of this study is to assess the impact of the possible reduction in Tariff Rate of sugar in Turkey under The World Trade Organization’s (WTO). Sugar is an important product for human life and obtained from sugar beet, sugarcane, starch-based sweeteners and chemical sweeteners. In almost all countries a protected product and 70% of world production is consumed in the domestic markets of the countries and remaining 30% share in the sugar trade between countries as an important product.Sugar is obtained from sugar beet in Turkey and it’s Tariff Rate is 135%. Under the title of market access in WTO, tariff reduction for products which are protected by more than 130% is 46% in developing countries. In this study; there are four model considered such as production, consumption, import and export and analyzed with 2 different scenarios which are zero Tariff Rate and prices after 46% discount on Tariff Rates of sugar. Partial equilibrium model was used. According to research findings; in each of two scenarios consumer welfare is observed to be increasing but these increases remain in low level. Producer and social welfare have emerged negatively in all three scenarios and the negative effect has been observed.